Mitral Annulus Calcium Score: An Independent Predictor of New Conduction System Abnormalities in Patients After Transcatheter Aortic Valve Implantation. (January 2019) - Brodov, Yafim; Konen, Eli; Di Segni, Mattia; Samoocha, David; Chernomordik, Fernando; Barbash, Israel; Regev, Ehud; Raanani, Ehud; Guetta, Victor; Segev, Amit; Fefer, Paul; Glikson, Michael; et al.
Abstract : Background: The risk of conduction system abnormalities (CSA) after transcatheter aortic valve implantation remains high. We aimed to evaluate the impact of mitral annular calcium (MAC) score on the development of CSA after transcatheter aortic valve implantation. Methods: Consecutive patients (n=168), with severe AoV stenosis, without prior CSA, underwent computed tomography transcatheter AoV implantation followed by device implantation; CoreValve (n=72) and SAPIEN (n=96). MAC, AoV, and left ventricular outflow tract calcium (Ca++) scores were quantitated from noncontrast ECG-gated computed tomography using Agatston method. The primary end point was a combination of complete left bundle branch block or high-degree atrioventricular block. Logistic regression was used to analyze the predictive value of Ca++ scores of different locations. Results: The primary end point was documented in 62% of the fourth quartile MAC score (>2700) patients as compared with 31% of the first quartile (<140); P =0.03. Logistic regression analysis documented MAC score as an independent predictor either of primary end point as a continuous variable (odds ratio: 1.02, 95% [CI]: 1.00 – 1.03, p = 0.021) or as quartile cutoffs, whereas Q4 was a strong and independent predictor (odds ratio: 3.69, 95% [CI]: 1.37 – 9.95, p = 0.010). Conclusions: MAC score was found to be an independent predictor of CSA in patients undergoing transcatheter aortic valve implantation without preexisting CSA. Therefore, the current study suggests that patients with high MAC score category (fourth MAC score quartile) should be considered at high risk for CSA, warranting closer monitoring. Clinical Trial Registration: URL:https://www.clinicaltrials.gov. Unique identifier: NCT02023060.